Statica e dinamica giuridiche dei trust alla luce della prospettiva comparatistica - Marone, Fulvio (Universita degli studi di Salerno, 2020)
2018 - 2019 Ph.D. thesis examines both Italian trust and so-called trust interno. Legai scholars theorize that Italian legai order provides rules for thè trust, such as Law no. 364/1989, Artide 2645 ter of thè Italian Civil Code, Law no. 112/2016. Thè dissertation is also connected to thè comparative perspective. Thè essay analyses thè legai nature of thè trust, with regard both to thè inter vivos field and thè law of succession. [edited by Author] XXXII ciclo